Effect of synthetic colloid administration on hemodynamic and laboratory variables in healthy dogs and dogs with systemic inflammation. (5th May 2014) - Gauthier, Vincent; Holowaychuk, Marie K.; Kerr, Carolyn L.; Bersenas, Alexa M.E.; Wood, R. Darren
Abstract Objective To compare the effects of administering equal volumes of isotonic crystalloids and synthetic colloids on hemodynamic and laboratory variables in healthy dogs and dogs with systemic inflammation. Design Randomized, placebo‐controlled, blinded study. Setting Comparative clinical research facility. Animals Sixteen adult purpose‐bred Beagles. Interventions Dogs were first randomized to receive either lipopolysaccharide (LPS; 5 μg/kg, IV) or an equal volume of placebo (0.9% NaCl, IV). Dogs were then randomized into 1 of 2 groups receiving fluid resuscitation with either 40 mL/kg IV isotonic crystalloid (0.9% NaCl) or synthetic colloid (tetrastarch). After a 14‐day washout, the study was repeated such that dogs received the opposite treatment (LPS or placebo) and the same resuscitation fluid regimen. Vital signs (heart rate (HR), oscillometric blood pressure) were measured and blood samples were collected for PCV, total plasma protein (TPP), serum lactate concentration, and colloid osmotic pressure (COP) measurements. Measurements and Main Results Healthy (placebo) dogs had similar decreases in PCV and TPP after administration of either fluid. Tetrastarch administration was associated with a larger increase in HR, systolic blood pressure, and mean blood pressure. Dogs with systemic inflammation had similar increases in systolic blood pressure and decreases in PCV, TPP, and lactate after administration of either fluid. Tetrastarch administration caused greater immediate increase in HR and mean blood pressure compared to 0.9% NaCl. In all dogs, 0.9% NaCl administration decreased COP and tetrastarch administration increased COP. Conclusions Resuscitation with equal volumes of 0.9% NaCl and tetrastarch caused similar changes in hemodynamic and laboratory variables in dogs with LPS‐induced systemic inflammation; however, larger increases in HR and blood pressure were seen within the first 2 hours following tetrastarch administration compared to 0.9% NaCl. Tetrastarch administration increased COP in all dogs, despite a decrease in TPP.